World cinema and the visual arts [ - Gallagher, David (New perspectives on world cinema, 2012)
World Cinema and the Visual Arts' combines new analyses of two subjects of ongoing research in the field of humanities: cinema and the visual arts. The films analysed encompass a wide geographical base, and have been drawn from a diverse array of cultural traditions